Enhancing the performance of polyfarnesene-based bio-rubbers with surface-modified cellulose nanocrystals and nanofibers - Luis Valencia; Ilse Magaña; Marisol Gálvez; Francisco Javier Enríquez-Medrano; Teresa Córdova; Cristal Cabrera; José Luis Olivares Romero; Héctor Ricardo López-González; Ramón Díaz de León (Scientific Reports)
Abstract As the rubber industry seeks sustainable alternatives to mitigate its environmental impact, this study introduces a biobased approach using polyfarnesene rubber reinforced with plasma-modified cellulose nanocrystals (MCNC) and nanofibers (MCNF). The nanocellulose was modified by plasma-induced polymerization using trans-β-farnesene and was characterized by FTIR, XPS, XRD, TGA, and SEM to confirm the grafting of farnesene-derived polymer chains onto the cellulose surface, demonstrating the successful modification and integration of the nanoparticles. Polyfarnesene bio-based rubbers were synthesized through two different polymerization techniques: solution-based coordination polymerization (PFA1) and emulsion-based free radical polymerization (PFA2). The modified nanoparticles were incorporated into these rubber matrices at 2–12 wt% and vulcanized by incorporation of sulfur. The performance of bio-rubbers reinforced with cellulose nanoparticles was analyzed by tensile test and dynamic mechanical analysis (DMA). Mechanical tests focused on tensile strength, Young’s modulus, and elongation at break showed that incorporation of 12 wt% modified MCNF into the PFA1 and PFA2 increased tensile strength by 56% and 22%, and Young’s modulus by 27% and 58%, respectively (compared to the neat rubber matrix), while elongation at break decreased with increasing MCNF content. The addition of MCNC into PFA1 and PFA2 improved the deformation resistance values of 205% for PFA1-MCNC12% and 49% for PFA2-MCNC12%. Dynamic mechanical analysis showed an increase in storage modulus and a shift towards higher glass transition temperatures, indicating stronger filler-matrix interactions. The results demonstrate that plasma-modified cellulose nanoparticles effectively enhance the mechanical properties of polyfarnesene bio-rubbers, offering a sustainable alternative with performance competitive to synthetic rubbers.